Morpho-sedimentological and vegetational characterization of Grande beach at São Francisco do Sul Island (Santa Catarina, Brazil). Issue 2 (13th November 2018) - Alquini, Fernanda; Bertoni, Duccio; Sarti, Giovanni; Vieira, Celso Voos; Melo Júnior, João Carlos Ferreira
ABSTRACT: A multidisciplinary study based on several digital (geology, lithology, shoreline evolution, photo-interpretation of aerial and ortho-photographs) and field (topographic and vegetational surveys, grain-size analysis) datasets prompted new insights to a better definition of the processes in action at the Grande beach at São Francisco do Sul Island (Santa Catarina, Brazil). The resulting data enabled us to produce a multi-thematic map at 1:50, 000 scale that might be useful in assisting decision-makers to manage the coastal system, taking into account involved factors at once and not separately. In addition, the map may be implemented and integrated with new information, since the database is provided in geographical information system. The results confirmed the importance of addressing coastal systems with a multi-faceted approach that can be applied everywhere, not only in settings similar to São Francisco do Sul Island.